Territorializing effects of global standards: What is at stake in the case of 'sustainable' palm oil?. Issue 104 (August 2019) - Ruysschaert, Denis; Carter, Caitriona; Cheyns, Emmanuelle
Highlights: RSPO standardisation spatially re-distributes power with territorial effects. Strategic and socio-technological processes are central to this territoralisation. RSPO weakness stems from territorialised governing, not spontaneous market outcome. Actors build access to natural resources and political capacity to counter critique. We reveal dominant RSPO territorial sustainability visions and their alternatives. Abstract: Global private sustainability standards in agriculture today govern a range of commodities produced in the tropics. Our study analyses the most well-established of these standards, namely the Roundtable on Sustainable Palm Oil (RSPO). We show how, far from being a market device restricted to re-organising global markets in palm oil, RSPO standardisation has wider consequences spatially re-distributing power with territorial effects. Territorialisation occurs through two processes: a strategic and operational process linked to the fabrication and application of procedural rules; a socio-technological process linked to the valorisation of managerial approaches to sustainability. Over time, these twin processes have institutionalised a transnational political space of action with territorial properties. These include: new frontiers of political authority de-bordering national jurisdiction (geographically connecting local scale oil palm estates and plantations with a transversal global supply chain stretching from producing to consuming countries); historical connection; internal coherence and imposition of managerial practices and discourses, including managerial constructions of interdependencies between people, nature and artefacts; prime beneficiaries (large southeast Asian growers, international environmental NGOs and (mainly) European downstream firms); marginalised people (independent smallholders and communities in Malaysia and Indonesia). In this manner, RSPO reinforces its political power and authority over a managerial form of sustainability of palm oil production through territorialising it. Ultimately, this transnational political space of action comes into interaction (and, potentially, conflict) with other political spaces of action and territorial projects as pursued by local people, other NGOs or Malaysian and Indonesian state governments.